British Association of Perinatal Medicine 2018
DOI: 10.1136/archdischild-2018-rcpch.186
|View full text |Cite
|
Sign up to set email alerts
|

G191 Catcam: a new solution for congenital cataract screening?

Abstract: AimsCongenital cataract is the leading cause of childhood blindness worldwide; surgery before 9–10 weeks of age is necessary to optimise visual outcome. We investigated the accuracy of the Newborn Infant Physical Examination (NIPE) red reflex test in the detection of cataracts and compared it to CatCam, a novel hand-held infrared digital imaging device.MethodsWe first reviewed the notes of all children having cataract surgery under 3 years of age over a 2 year period to determine how and when referral had occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study indicated that the sensitivity and specificity of RRT for detecting media opacity was 71% and 62% respectively. 29 Although, a recent study reported the reliability of a modified direct ophthalmoscope as 92.7% in congenital cataract diagnosis; detailed examination by an ophthalmologist is still the most definitive method. 30 In our study, 14 preterms with congenital cataract and 8 PFV cases complicated with lens opacity were detected and 14 of them required surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that the sensitivity and specificity of RRT for detecting media opacity was 71% and 62% respectively. 29 Although, a recent study reported the reliability of a modified direct ophthalmoscope as 92.7% in congenital cataract diagnosis; detailed examination by an ophthalmologist is still the most definitive method. 30 In our study, 14 preterms with congenital cataract and 8 PFV cases complicated with lens opacity were detected and 14 of them required surgical intervention.…”
Section: Discussionmentioning
confidence: 99%